Secretion of CyaA-PrtB and HlyA-PrtB fusion proteins in Escherichia coli: involvement of the glycine-rich repeat domain of Erwinia chrysanthemi protease B. - Létoffé, S (1992)
Protease B from Erwinia chrysanthemi was shown previously to have a C-terminal secretion signal located downstream of a domain that contains six glycine-rich repeats. This domain is conserved in all known bacterial proteins secreted by the signal peptide-independent pathway. The role of these repeats in the secretion process is controversial. We compared the secretion processes of various heterologous polypeptides fused either directly to the signal or separated from it by the glycine-rich domain. Although the repeats are not involved in the secretion of small truncated protease B carboxy-terminal peptides, they are required for the secretion of higher-molecular-weight fusion proteins. Secretion efficiency was also dependent on the size of the passenger polypeptide.